Answer:
x = 16
Explanation:
3√x = x - 4
Raise the equation to the second power.
(3√x)² = (x - 4)²
9x = x² - 8x + 16
Rewrite the equation with the values on the left.
-x² + 17x - 16 = 0
x² - 17x + 16 = 0
Factor.
(x - 16)(x - 1) = 0
Set each part equal to 0.
x - 16 = 0
x = 16
x - 1 = 0
x = 1
Your solutions are 16 and 1, but it doesn't end there. Both of these may not satisfy the original equation, so plug them back in.
3√x = x - 4
3√16 = 16 - 4
3(4) = 12
12 = 2
16 is a solution.
3√x = x - 4
3√1 = 1 - 4
3(1) = -3
3 ≠ -3
1 is NOT a solution.